differentiate arsinh(cosx))

let's start by defining y = arsinh(cos(x)). taking sinh of both sides gives sinhy = cosx. (since sinh(arsinhz) = z). Now we can differentiate both sides wrt x. The RHS differentiates to -sinx. We can use the chain rule for the LHS: d/dx = dy/dx *d/dy.so d/dx(sinhy) = dy/dx d/dy(sinhy) = dy/dx coshy. so dy/dx = -sinx/coshy. Now coshy = sqrt(1+(sinhy)^2) = sqrt(1+(cosx)^2).So dy/dx = -sinx/sqrt(1+(cosx)^2).

Related Further Mathematics A Level answers

All answers ▸

Evaluate ∫sin⁴(x) dx by expressing sin⁴(x) in terms of multiple angles


Find the four roots of the equation z^4 = + 8(sqrt(3) + i), in the form z = r*e^(i*theta). Draw the roots on an argand diagram.


Prove by induction that n! > n^2 for all n greater than or equal to 4.


Why is the argument of a+bi equal to arctan(b/a)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences